Determination of apparent and standardized ileal digestibility of amino acids in corn HP-DDG fed to growing pigs - da Motta, Stephane Alverina Briguente; Barcellos, Joyce; Lourenço, Antônio Carlos Macedo; Ramos, Bruno Teixeira; Lima, Ideraldo Luiz; Mike, Brian Patrick; Rennó, Luciana Navajas; Hannas, Melissa Izabel (Frontiers in Animal Science, 2024)
The corn-based ethanol production industry provides co-products with potential value as animal feed. However, the nutritional value of these co-products should be adequately determined for sustainable implementation in swine diets. Therefore, a study was conducted to determine the concentration of amino acids (AA), apparent ileal digestible amino acids (AID), and standardized ileal digestible amino acids (SID) and crude protein (CP) in corn distillers dried grains with high protein (corn HP-DDG) for pigs. Six growing pigs (initial body weight: 46.30 ± 2.14 kg) were surgically fitted with a T-cannula at the distal ileum and allotted to a duplicate 2 x 3 incomplete Latin Square Design. Diets containing corn HP-DDG as the only AA source and a nitrogen-free diet (NFD) were formulated. Corn HP-DDG was used as a test ingredient to replace 40% of starch in NFD, and titanium dioxide (0.5%) was added as an indigestible marker to both diets. Pigs were fed between 08:00 and 18:00h during five days of adaptation and a sequence of two days of ileal digesta collection. On an as-fed basis, the analyzed chemical composition of corn HP-DDG was 40.